PEMBUATAN CRACKERS JAGUNG DAN PENDUGAAN UMUR SIMPANNYA DENGAN PENDEKATAN KADAR AIR KRITIS [Production of Corn Cracker and Prediction of Its Shelf Life Using a Critical Moisture Approach] - . Sugiyono; Esther Mariana; Aton Yulianto (Jurnal Teknologi dan Industri Pangan, 2013)
The objectives of this research were to produce crackers based on corn flour and to predict its shelf life using a critical moisture approach.The best crackers were produced from a mixture of 60% corn flour and 40% glutinous rice flour. The products had a puffing ratio of 11%, crispiness of 250.8 gf and hardness of 384.7 gf. The corn crackers had better crispiness and hardness than those of commercial rice crackers. The moisture sorption isotherm curve of corn crackers could be described using a Hasley model. Using the critical moisture approach, corn crackers packaged in a metallized plastic and stored at 30°C and 75% relative humidity had a shelf life of 366 days. If the products were stored at 85% relative humidity, the product shelf life would be 150 days.